ASSESSMENT OF DENTAL ANXIETY IN PRE AND POST DENTAL TREATMENT - Shafaq Noori; Sundas Aasim; Abdur Rehman; Amaan Ullah Siddiqui (ziauddin University, 2024)
Background: Dental anxiety is an affecting condition that aid normal persons to protect themselves in opposition to multiplicity of threats and pressure. The study aimed to assess the prevalence of dental anxiety in pre and post dental treatment. Methods: A total of 210 patients were selected who are first and/ or second visited for any dental complain. The selected patients were divided into two groups. Group I: pre-treatment Group II: post-treatment. In pretreatment 42.8 % male and 3.2% female was selected for the study. While 20.9 % male and 23.8 % female were selected for study in post-treatment. Corah's Dental Anxiety Scale (DAS) is used to assess the anxiety among the study population. Anxiety level is categorized into moderate, high and severe anxiety score. Results: The research found significant results in moderate, high and severe anxiety score in pre treatment group while severe anxiety score was observed in post-treatment group. Significant mean differences were observed in pre and post treatment anxiety group when compared with control while no changes were observed between pre and post treatment. A strong but negative correlation was observed in 15-20 years (male) with anxiety score in pretreatment group while negative strong correlation was observed in (female) 20-30 years anxiety post treatment group. A strong negative correlation was observed in unmarried / married male and female in pretreatment group. While positive strong correlation was observed in married female in post-treatment group. Conclusion: The results of this study are not representative of dental anxiety subjects during pre and post treatment. The prevalence of dental anxiety is obvious in married female however; it may be controlled by the positive attitude and behavior of dentists.